Research Advances in Traditional Chinese Medicine for Postpartum Arthralgia - Lu, Miaojie; Tai, Yingchun (Journal of Contemporary Medical Practice, 2025)
Postpartum arthralgia represents a prevalent puerperal disorder characterized by myoarthralgia, paresthesia, and heaviness in extremities, significantly compromising postpartum recovery and quality of life. TCM pathogenesis has evolved from the qi-blood deficiency with wind-pathogen invasion theory documented in “Treatise on the Origins and Manifestations of Diseases” to the contemporary systemic recognition of “root deficiency with superficial excess” pathology. This review methodically examines therapeutic advances, including: On the one hand, Patho mechanism evolution: Classical concepts: Deficiency/Stasis/Pathogen triad, Modern expansions: Liver-qi stagnation & damp-heat pathogenesis; on the other hand, Multimodal interventions: Pharmacotherapy: Classical formulas (e.g., Astragali-Cinnamomi Five Substances Decoction) and empirical prescriptions, External therapies: Du-moxibustion, acupuncture. Clinical data demonstrate ≥90% efficacy through syndrome-differentiation protocols employing the “reinforcing healthy qi and eliminating pathogens” principle, showcasing advantages in holistic regulation and superior safety profile. This work provides evidence-based clinical references and identifies future research directions.